ANALISIS KRIMINOLOGIS PENYALAHGUNAAN KECERDASAN BUATAN DALAM KEJAHATAN SIBER - Rudi Nopiansyah; Mega Fitri Hertini; Parulian Siagian; Sri Ismawati; Herlina Herlina (IJTIMAIYAH Jurnal Ilmu Sosial dan Budaya, 2026)
The development of artificial intelligence (AI) has brought about significant transformations across various sectors, including the landscape of cybercrime. This study aims to analyze the phenomenon of AI misuse from a criminological perspective and its implications for criminal law in Indonesia. The research method employed is a qualitative approach using a literature review, drawing from reputable scientific literature, legal documents, and actual cases related to AI-based crimes. Research findings indicate that AI has fundamentally transformed the landscape of digital crime, serving not only as a tool of crime but also as an object of crime and a virtual offender. The misuse of AI encompasses various forms, ranging from deepfakes and automated phishing to adaptive algorithm-based hacking. From a criminological perspective, AI-based crime is influenced by a combination of individual, structural, and cultural factors, including high technological literacy among perpetrators, economic and ideological motives, and a digital environment characterized by anonymity and weak social control. Additionally, there is a shift in crime dynamics from manual actions toward automation, from personal risk toward distributed risk, and from individual crime toward network-based systemic crime. The implications of this research underscore that conventional criminal law has not yet been fully able to address the complexity of AI-based crimes, particularly with regard to the attribution of legal liability. Therefore, a paradigm shift in the law is needed that integrates criminological, technological, and ethical approaches, through the strengthening of adaptive regulations, the implementation of risk governance, and ethical accountability to protect society in the era of artificial intelligence. artificial intelligence, cybercrime, criminology, criminal law, legal liability